Infrastructure, institutions and identity - Determinants of regional development: Empirical evidence from Germany - Stefanie Gäbler (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2020)
Stefanie Gäbler prepared this study while she was working at the ifo Center for Public Finance and Political Economy. The study was completed in March 2020 and accepted as doctoral thesis by the Department of Economics at the University of Munich. It consists of six distinct empirical essays investigating various aspects of regional development using data from Germany. Chapters 2 and 3 investigate the impact of transport infrastructure in the form of an regional airport and highway expansion. Chapters 4 and 5 examine institutions at the local level, namely local public accounting standards and local election systems. Chapter 6 deals with the topic of regional identity. The chapters employ difference-in-differences, event study and synthetic control estimations to answer the respective research questions.
Keywords: D02; D72; D73; H40; H54; H70; H71; H75; H83; L93; O18; R50; Z19; Z38; 330; Airports; tourism; regional development; transportation infrastructure; highway; accessibility; tax factors; municipalities; local government; fiscal rules; public accounting; budget transparency; sustainability; government efficiency; accountability; direct election; constitutions; government form; economic performances; public services; common identity; regional identity; formation of identity; voter turnout; Germany; GDR; reunification; synthetic control method; differences-in-differences; event studies